Full-Stack React with Spring Boot - Olsen, Andy (Addison-Wesley Professional, 2021)
Sneak Peek The Sneak Peek program provides early access to Pearson video products and is exclusively available to Safari subscribers. Content for titles in this program is made available throughout the development cycle, so products may not be complete, edited, or finalized, including video post-production editing. 11 Hours of Video Instruction Build full-stack applications using React and Spring Boot. Overview: In recent years, React has emerged as a popular lightweight framework for implementing compelling web-based user interfaces. Using React you can easily integrate with back-end services via REST APIs, and Spring Boot is an excellent framework for implementing REST services. Spring Boot also provides an extremely efficient way to implement data-access logic to access a wide range of relational and NoSQL databases. This course explains how to dovetail React and Spring Boot to implement solid, performant, and extensible full-stack solutions. It is full of hands-on demos with in-depth explanations so you can see first-hand how to successfully build full-stack applications using React and Spring Boot. Taught by experienced trainer and author, Andy Olsen, this course is your complete guide to mastering React and Spring Boot systems to enable you to create enticing user interfaces with a solid and well-structured back end. Download the code files associated with this LiveLesson from https://www.informit.com/store/full-stack-react-with-spring-boot-livelessons-video-9780137508891 . About the Instructor Andy Olsen Ơ s a freelance consultant, instructor, and developer with more than 30 years of experience in IT. Andy began his professional career as a C/C++ developer and morphed into Java, C#, and other languages as the years and decades passed by. Andy is actively involved in a wide range of technologies including full-stack development, cloud native applications, data science, and more. Andy is passionate about technology education and runs training courses around the world across diverse market sectors. You can find Andy here: https://www.linkedin.com/in/andy-olsen-481496/ http://olsensoft.com/ Topics include Creating and running Spring Boot web applications Defining and managing components Accessing relational and NoSQL databases Implementing and consuming REST services Creating a React front end Consuming a REST API from React Implementing a compelling UI in React Skill Level: Intermediate Learn How To Create a ...